Association between obesity and fecundity in patients undergoing intrauterine insemination - LaTasha B. Craig, M.D; Christen L. Jarshaw, M.D; Karl R. Hansen, M.D., Ph.D; Jennifer D. Peck, Ph.D (Elsevier, 2023)
Objective: To determine if an association exists between body mass index (BMI) and fecundity after intrauterine insemination (IUI). Design: Retrospective cohort study. Setting: Academic-based fertility clinic. Patient(s): Patients undergoing IUI July 2007 to May 2012. Intervention(s): None. Main Outcome Measure(s): Primary outcome: live-birth rate (LBR) per IUI cycle; secondary outcomes: positive pregnancy test and clinical pregnancy rates (CPRs). Result(s): A total of 1959 cycles were performed on 661 women (mean age, 31.9 ± 4.9 years). When examined by obesity class, LBR and CPR were similar for women with class I, II, and III obesity when compared with women with normal BMI. However, class III obese women (adjusted risk ratio [aRR], 1.70; 95% confidence interval [CI], 1.12-2.59) had increased pregnancy rates compared with normal BMI, but no differences in pregnancy rates were observed for women with class I or II obesity. In addition, pregnancy rates (aRR, 1.50; 95% CI, 1.12-2.02) and CPR (aRR, 1.51; 95% CI, 1.07-2.14) were higher in overweight women relative to normal BMI. Notably, among patients with ovulatory dysfunction, CPRs after IUI were reduced by 43% in obese women (aRR, 0.57; 95% CI, 0.37-1.07), whereas women without ovulatory dysfunction were twice as likely to achieve a clinical pregnancy when they were obese (aRR, 1.96; 95% CI, 1.19-3.24). The CIs for the obesity risk ratios in each stratum of ovulatory function exhibited no overlap, suggesting evidence of potential effect modification by ovulatory function. Conclusion(s): LBRs after IUI were similar across BMI subgroups. This is in contrast to research of in vitro fertilization treatments showing lower LBR with increasing BMI. However, obesity may adversely affect IUI CPR in those with ovulatory dysfunction in particular. The reason for this discrepancy is unclear and warrants further study.